Managing bank capital : capital allocation and performance measurement - Matten, Chris (Chichester, West Sussex, UK ; New York : Wiley, 2000)
Explains proven techniques available in the management of bank capital that will help maximize shareholder value. This second edition has been fully updated to incorporate significant developments, such as the modeling of credit risk, and includes new sections with more technical information and advanced analysis.
Includes bibliographical references and index.
oif 11/07/2016
Loans
Keywords: Bank capital; Bank investments; Asset allocation; Asset-liability management; Risk management